Demystifying the low cost housing issues in Malaysia/Wan Sumayyah Syahidah Wan Mohamad, Mohd Rozaimy Ridzuan & Noor Amira Syazwani Abd Rahman - Wan Mohamad, Wan Sumayyah Syahidah; Ridzuan, Mohd Rozaimy; Abd Rahman, Noor Amira Syazwani (Universiti Teknologi MARA Cawangan Pahang, 2019)
A sound housing policy is always becoming a major priority for all governments around the world, especially in the endeavor to provide low cost housing for the low income group people. There is an urgent need for the government to build low cost housing as it offers affordable housing to the low income group. However, low cost housing is always associated with problems. Hence, the main objective of this concept paper is to identify issues that hampered the quality of low cost housing in Malaysia. A thorough review of literatures has been carried out and the findings are spelled out by classifying them into four categories: Maintenance and Management, Structural and Building Materials, Provision of Public Facilities, and External Environment. These are among the areas of concern that need to be rectified to ensure that low income earners are able to own a conducive house. This study concludes that exploring low cost housing residents’ feedback on the issues is effective in order to design a quality low cost housing. Without adequate, affordable and quality housing, even the right to live and definitely the quality of life can be seriously jeopardized.